ANALYSIS OF THE ROLE OF OWNER AND PROJECT MANAGER IN THE PERFORMANCE OF DESIGN AND BUILD CONTRACTS (CASE STUDY OF RUMAH SAKIT SURABAYA TIMUR (RSST) PROJECT) - Perdana, Dicky Rianda; Patriadi, Andi; Sajiyo, Sajiyo (Ridwan Institute, 2025)
The construction industry plays a significant role in infrastructure development, including healthcare facilities like hospitals. This research aims to comprehensively identify, analyze, and evaluate the impact of design and build risk factors on the time performance of hospital construction projects. The study focuses on two main objectives: first, to analyze the impact variables related to owner and project manager factors on project time performance; and second, to develop effective mitigation strategies to manage and minimize these risks during implementation. The analysis process included data cleaning and verification, validity and reliability testing, descriptive analysis, Pearson correlation analysis, and multiple linear regression analysis to evaluate the relationships between risk factors and the success of the hospital construction project. The results show that the Owner and Project Manager (PM) factors include several key variables with strong to perfect and significant correlations to project success, particularly key variables within each category. Project success is significantly influenced by the effective management of risk factors with high and significant correlatives, especially key variables in each category, namely, Project Management Competence (PM). This research contributes to the construction industry by providing insights and practical strategies tailored to the complexities of healthcare infrastructure, thereby advancing the development of risk management practices in this critical sector.